Effect of Service Quality on Coffee Based Economic Cluster Development on Farmers and other Stakeholders Satisfaction in Bondowoso District - Lya Aklimawati; Djoko Sumarno; Surip Mawardi (Indonesian Coffee and Cocoa Research Institute, 2015)
Economic cluster approach can be used to enhance economic growth of region by optimizing local resources. Coffee is one of plantation commodity which developed in Bondowoso district through economic cluster model. Low quality coffee beans and inefficiency marketing system were the basic problems at farmer level that pushed for developing economic coffee cluster. The aim of this research was to analyze the effect of service quality on economic coffee cluster development toward farmers and stakeholders satisfaction. This research was carried out at Bondowoso District, East Java. Direct observation and interviews coffee farmers and stakeholders using close questions was conducted in this study. Data collected consisted of primary and secondary data. The number of respondents were 47 stakeholders consisted of 5 officers from BI Jember, 5 officers from Dishutbun Bondowoso, 2 officers from Perum Perhutani and 35 farmers. Respondents selection was based on convenience sampling method. Primary data was analyzed by using correlation and multiple linier regression analysis. The result showed that the relationship between dimensions of service quality with each other varies from weak to strong. Stakeholders satisfaction (included farmers) on economic coffee cluster implementation was influenced significantly by tangible at significance level 5%. While reliability, responsiveness, assurance and empathy has no effect to stakeholders satisfaction at significance level 5%. Keyword : satisfaction, farmer, stakeholder, service quality, economic cluster, coffee